Validity Of The Establishment Of A Limited Liability Company (PT) By One Person - Irwan Haryowardani (CV. AFDIFAL MAJU BERKAH, 2022)
The establishment of a limited liability company that is not made with a notarial deed, the establishment of a limited liability company is considered never to exist, because it is considered not to meet the elements of the establishment of a limited liability company, it can be a reason for third parties who have an interest to request the dissolution of the limited liability company through the District Court. The fulfillment of these material conditions has not made the institution a legal entity, if the formal requirements of a legal entity have not been met. The formal requirement is the recognition of the state or law stating that the institution is a legal entity. This research is a descriptive study that aims to find a rule of law, legal principles, and legal doctrines to answer legal issues faced by collecting materials sourced from legal materials based on concepts, theories, laws and regulations, doctrines, legal principles, expert opinions or views of researchers themselves, relating to the validity of the establishment of a limited liability company (PT) by one person. The validity of the establishment of a Limited Liability Company by one person in the job creation law refers to Article 153A which states that a company that meets the criteria of Micro and small businesses can be established by 1 (one) person. After the ratification of Law Number 11 of 2020 on job creation, the exception regarding the establishment requirement in Article 109 number 5 that “companies that meet Micro and small businesses can be established by 1 (one) person, which is electronically registered with the minister and can only be established by 1 (one) within a period of 1 (one) year.